Interventions Against West Nile Virus, Rift Valley Fever Virus, and Crimean-Congo Hemorrhagic Fever Virus: Where Are We? - (:unkn) unknown (MARY ANN LIEBERT, INC, 2010)
ARBO-ZOONET is an international network financed by the European Commission's seventh framework program. The major goal of this initiative is capacity building for the control of emerging viral vector-borne zoonotic diseases, with a clear focus on West Nile virus, Rift Valley fever virus, and Crimean-Congo hemorrhagic fever virus. To evaluate the status quo of control measures against these viruses, an ARBO-ZOONET meeting was held in Istanbul, Turkey, from 19 to 20 November 2009. The symposium consisted of three themes: (1) vaccines: new and existing ones; (2) antivirals: existing and new developments; and (3) antivector vaccines. In addition, a satellite workshop was held on epidemiology and diagnosis. The meeting brought together foremost international experts on the subjects from both within and without the ARBO-ZOONET consortium. This report highlights selected results from these presentations and major conclusions that emanated from the discussions held.
Keywords: antiviral; ARBO-ZOONET; Crimean-Congo hemorrhagic fever virus; Rift Valley fever virus; Vaccine; Vector; West Nile virus; RECOMBINANT VACCINE; IMMUNE-RESPONSES; NEUTRALIZING ANTIBODIES; ORAL RIBAVIRIN; SAUDI-ARABIA; NSS PROTEIN; EFFICACY; RNA; REPLICATION; RESCUE